Analisis Manfaat Penerapan Sistem Informasi Kesehatan dalam Pengolahan Data Pasien di Klinik - Dwi Syahputri Purba; Sri Hajijah Purba; Jihan Mawaddah Pane; Bunga Nurjannah Gea (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
The development of information technology has a significant impact on data management in the health sector, including clinics. This study aims to analyse the benefits of implementing a health information system in patient data processing in a clinic. The method used was literature review by collecting national research articles published between 2016 and 2024 and relevant to the topic under study. The results showed that the application of information systems in clinics can improve the efficiency of the patient registration process, accuracy and security of data storage, and improve the quality of health services. The system also facilitates report generation and data analysis that supports managerial decision-making and minimises errors in data processing. Thus, the implementation of an integrated information system can improve service quality and patient satisfaction at the clinic.